Pengukuran Efektivitas Kemasan Tens Coffee melalui Importance Performance Analysis (IPA) dan Hubungannya dengan Efisiensi Rantai Pasok - Utami, Adita Evalina Fitria; Yamin, Iqbal; Gultom, Pormauli (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Packaging plays a strategic role in preserving product quality, shaping consumer perception, and supporting supply chain efficiency, particularly in the ready to drink coffee industry. This study aims to evaluate the performance and importance of Tens Coffee packaging attributes and to identify improvement priorities. This research employs a descriptive quantitative approach using a Likert scale questionnaire distributed to 165 Tens Coffee consumers selected through accidental sampling. Data were analyzed using Importance Performance Analysis (IPA). The results indicate that packaging design and product protection performance meet consumer expectations. However, ease of opening and environmentally friendly materials show high importance but insufficient performance, making them key improvement priorities. These findings suggest that packaging quality is closely related to supply chain efficiency and sustainability. Further research is recommended to explore alternative materials and ergonomic packaging designs to enhance consumer satisfaction and operational efficiency.